A two-way relationship between the head and neck cancer and esophageal cancer. (October 2019) - Sharma, Mohit; Radhakrishnan, Raghu
Highlights: SPEC and SPLC have a 31–105% higher risk of death compared to those without SP. SP in HNC patients have shown to be associated with younger age. The surveillance of hypopharynx and esophagus is recommended in patients with PHNC.